Features of Tomato Protection in Protected Cultivation: Biotic Factors and Regulation (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
Abstract. The issue of tomato plant protection in greenhouse vegetable production is driven by the high stability of pest and pathogen populations and the insufficient effectiveness of existing regulatory approaches. Purpose of this study is to synthesize contemporary scientific approaches to phytosanitary protection of tomato under protected cultivation conditions and to substantiate integrated strategies for controlling major harmful organisms and diseases. Methods. A systems approach underpinned the study, in which the greenhouse agroecosystem was considered as an integrated system of interactions between biotic and abiotic factors. An analytical method was used to synthesize published data on tomato pests and their control strategies. A comparative method was applied to evaluate the effectiveness of biological, chemical, and integrated plant protection systems. System analysis enabled the assessment of interrelationships among components of greenhouse protection measures. A structural-logical method was employed to reconstruct the sequence of implementing protective interventions. The synthesis method facilitated the generalization of results and the formulation of coherent conclusions. The evidential base comprised scientific publications, data on pest biology, and information on technologies for the application of plant protection products. Results. It has been established that in glasshouse environments a stable complex of phytophagous pests and pathogens develops, in which tomato moth (Tuta absoluta) plays a dominant role, characterized by high reproductive capacity and rapid population growth throughout the year. Its damage is expressed through systemic injury to the leaf apparatus and generative organs, leading to a substantial reduction in photosynthetic activity, disruption of fruit formation, and the development of secondary infections, while severe infestations result in significant yield losses. An additional phytosanitary risk is posed by whitefly (Bemisia tabaci), which combines direct feeding on plants with the transmission of viral infections and the induction of physiological stress, manifested in growth suppression, reduced productivity, and deterioration of product quality. Thrips and spider mites impose a long-term cumulative stress on plants, causing disruption of water balance, reduction in chlorophyll content, and degradation of the leaf apparatus, thereby markedly decreasing the photosynthetic efficiency of the agroecosystem. The Tomato brown rugose fruit virus (ToBRFV) is characterized by high persistence under greenhouse conditions and predominantly mechanical transmission, which precludes its direct eradication and determines the leading role of preventive measures within protection systems. It has been demonstrated that the most effective strategy is an integrated approach combining biological control agents, selective chemical compounds, and physical control methods, including ultraviolet light traps that reduce adult populations and disrupt pest reproductive cycles. Conclusions. The synthesis of results indicates that protection efficiency is determined by early detection of harmful organisms, the combination of multiple control mechanisms, and systematic monitoring of the phytosanitary status of the greenhouse agrocenosis. The practical significance lies in the applicability of the findings for optimizing integrated tomato protection systems in hydroponic greenhouses and enhancing their phytosanitary stability.
Keywords: tomato; glasshouse greenhouses; hydroponics; integrated plant protection; Tuta absoluta; Bemisia tabaci; plant viral infections; biological control; entomophages; phytosanitary monitoring